CREATING SPACE FOR MORECOOPERATION IN BUENOS AIRES: CIVIL SOCIETY PARTICIPATION IN LOCAL PUBLIC POLICYMAKING - Liberman, Alejandro (Estado, Gobierno y Gestión Pública, 2014)
This project analyzes new ways of participationand its impact on local government in the city of Buenos Aires. Applying qualitative methodology, particularly in the first and only case study of its kind, the paper offers adescription and evaluation of the institutional process designed to engage organized civil society, and to increase cooperation with new forms of mediation within the new participatory framework of representative local democracy in place since 1996. Specifically, the local Strategic Planning Council will be evaluated and appraised by analyzing the goals and of the general strategic plan for the period 2004 to 2010.